ACUTE HF score, a multiparametric prognostic tool for acute heart failure: A real-life study. (1st December 2019) - Cameli, Matteo; Pastore, Maria Concetta; De Carli, Giuseppe; Henein, Michael Y.; Mandoli, Giulia Elena; Lisi, Edoardo; Cameli, Paolo; Lunghetti, Stefano; D'Ascenzi, Flavio; Nannelli, Chiara; Rizzo, Luisa; Valente, Serafina; et al.
Abstract: Background: Acute heart failure (AHF) is the first cause of hospitalization for over-65 individuals, associated with high mortality and readmission rate. The aim of this study was to assess the prognostic value of a multiparametric score combining clinical, biochemical and echocardiographic indexes in AHF for clinical practice. Methods: 830 patients hospitalized for AHF were enrolled. Exclusion criteria were: active neoplasms; previous heart transplantation or left ventricular assist device implantation. Different variables were analyzed: etiology of AHF, clinical and biochemical data, lung congestion on chest-X ray, echocardiographic parameters and administered therapy. The endpoints were: all-cause mortality at 30 days, 6 months and 5 years and the duration of hospitalization. Results: 771 patients met eligibility criteria. Using the univariate and multivariate analysis the indexes with the best correlation with outcome were discretized and used to create the ACUTE HF score, computed as: 1.4*[serum creatinine>2 mg/dl] + 0.8*[ejection fraction<30] + 0.7*[age > 76] + 0.7*[prior hospitalization for AHF] + 0.9*[prior stroke/transient ischemic attack] + 0.5*[more than moderate mitral regurgitation] + 0.8*[use of non-invasive ventilation] and used to divide patients into 3 groups according to the risk of 6-months mortality. With the receiver operating curves and Kaplan-Meier analysis, this score proved to have a high predictive power for mortality at 30 days, 6 months and 5 years from hospitalization, and for event-free survival rates, providing a risk stratification capability superior to that of single variables. Conclusions: The ACUTE HF score could be a complete and useful tool for assessing prognosis of AHF patients. It could represent a step in the long standardization pathway of prognostic protocols for AHF. Highlights: Clinical and echocardiographic data can be combined in a risk score for acute heart failure. Indexes with the best predictive power at uni- and multi-variate analysis created ACUTE-HF score. ACUTE-HF score showed a strong prognostic power and correlation with event-free survival rates. Our score provided a good stratification in three risk groups, superior to that of single variables.